Το "ενετικό" κτίριο στο ιστορικό κέντρο του Ναυπλίου - Μακρής, Παναγιώτης (Σχολή Αρχιτεκτόνων Μηχανικών, 2017)
This study explores the condition and architectural history of a very important historic building in the old city of Nafplio. Its architectural features and structural system are surveyed in detail as well as its relation with an equally important former mosque which now serves as the cathedral of the city. A preliminary dendrochronology report as well as the historical context in which the building evolved over time are also included. The urban and architectural surveys are followed by a restoration proposal supported by a structural analysis of the current state and an exploration of the viability of the proposed timber structural elements. This project is the result of the cooperative work between Panagiotis Makris and Amalia-Maria Konidi.